(untitled) (Hekima Review, 2013)
“Previous models of sanctity tended to emphasize a world-denying as asceticism; today we need examples of discipline and self-denial in service to the world and in solidarity with a suffering humanity. There are countless saints who exhibited in virtue of charity; we need saints who combine charity with a prophetic thirst for justice... We need examples of holiness beyond the cloister: saints immersed in worlds of art, literature, scholarship, in political struggle, and in everyday life. We need prophets who challenge the church as well as the world to better reflect the justice and the mercy of God. We need the witness of the martyrs, ancient and new, who have laid down their lives for their faith and for their neighbors. We must attend to the vision of the mystics, who see through the shade of everydayness and so remind us of the God who is ever greater than our theologies or our imaginations.”